Translation And Validation Of Bahasa Indonesia Version Of Mental Health Literacy In Adolescent - Juniarni, Lia; Kanathasan, Jayasree S; Nallappan, Devi (Holistic Nursing Plus, 2025)
Background: Mental health literacy (MHL) is crucial for adolescents to recognize, manage, and prevent mental health issues. In Indonesia, increasing adolescent mental health challenges and limited culturally adapted MHL tools highlight the need for a validated Mental Health Literacy Scale (MHLS) in Bahasa Indonesia. Objective: This study aimed to translate, culturally adapt, and validate the MHLS for Indonesian adolescents to assess their mental health literacy accurately. Methods: The study followed a three-stage validation process: translation, cultural adaptation, and content validation with a sample of 435 adolescents. Confirmatory Factor Analysis (CFA) was conducted to assess construct validity, and Cronbach’s alpha was calculated for reliability. Results: The translated MHLS showed high content validity (CVI ≥ 0.87) and good construct validity with fit indices (RMSEA = 0.046, CFI = 0.956). Internal consistency was high (Cronbach's alpha = 0.907), indicating reliability. Conclusion: The Bahasa Indonesia version of MHLS is a valid and reliable tool for assessing mental health literacy in Indonesian adolescents, supporting culturally relevant interventions.